2007
DOI: 10.1016/j.nima.2007.05.166
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the angular profile of the reflection of xenon scintillation light

Abstract: A chamber designed for measuring the angular distribution of reflected ultraviolet vacuum light is described. We report first measurements of the reflection profile of xenon scintillation light by a polished copper surface and by polytetrafluoroethylene (PTFE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Recently, there have been new efforts to determine the reflectivity profiles of some materials of interest for detector construction at the xenon emission wavelength [171,166,172]; some results are shown on the right panel of Figure 16. Figure 16.…”
Section: Light Propagationmentioning
confidence: 99%
“…Recently, there have been new efforts to determine the reflectivity profiles of some materials of interest for detector construction at the xenon emission wavelength [171,166,172]; some results are shown on the right panel of Figure 16. Figure 16.…”
Section: Light Propagationmentioning
confidence: 99%
“…The reflectance model used in our simulations takes into account both specular and diffuse components. Since Spectralon® surfaces are known to be rough, we used the reflectance model proposed in our previous work [32], which adapts equation 1 to account for roughness. To characterize the roughness of the Spectralon® surface, we employed a gonioreflectometer as described in ref., [18], and found that the surface profile follows the Trowbridge-Reitz distribution [33] with a roughness parameter σ α of 0.17.…”
Section: B the Monte-carlo Simulationmentioning
confidence: 99%
“…A detailed knowledge of the angular reflectivity profiles is also important for correct modeling of the detector response. Recently, there have been new efforts to determine the reflectivity profiles of some materials of interest for detector construction at the xenon emission wavelength [171,166,172]; some results are shown on the right panel of Figure 16. .…”
Section: Light Propagationmentioning
confidence: 99%